Symposium 4: The Networked Learning Forum 2021: Early researchers’ expectations and experiences - Calleja, James; Cutajar, Maria (Proceedings of the International Conference on Networked Learning, 2024)
Early researchers (ERs) benefit from opportunities to present, discuss and develop their research work. A typical professional learning experience that may support ERs is their active participation in conferences. In this paper, we report on the expectations and experiences of five ERs who participated in the Networked Learning (NL) Forum 2021 by presenting their research and then having opportunities to gain feedback and insights from one-to-one interactions with more knowledgeable others and the larger community within the event itself. We draw on qualitative research with our main data sources being a pre- and a post-event online survey. We were interested to explore the extent to which the experiences described by the five ERs participants met their pre-event perceived views and expectations. While the pre-event survey delved into the participants’ professional background, motivations for participation and expectations, the post-event survey targeted participants’ perceptions about their learning and potential takeaways. Findings indicate that the five ERs saw their participation as an opportunity for their professional development and as an avenue to make and create professional connections with others in the same field of research. Most notably, they expected feedback from the NL Forum 2021 community and their interactions with field experts (referred to also as knowledgeable others) as support that could help them gain new and deepened insights for developing their research ideas and work. In describing their experiences (post-event), participants highlight opportunities for one-to-one conversations with experts, discussions in small groups, individual and collective reflections, connections with other ERs and the possibilities for expanding their professional learning networks. These findings highlight the importance of design features when offering events specifically targeted for ERs. In particular, findings indicate that creating an intimate, interactive and safe environment is essential for ERs to feel confident to present their research, critically analyse new perspectives and knowledge shared by others, and eventually acquire new knowledge.